Design of Activity Book for Study Tour for 12-Year-Old Children at The Loka Jala Crana Museum - Agnes Veronica Sungkono; Bayu Dwi Nurwicaksono (Universitas Negeri Surabaya, 2025)
Loka Jala Crana Museum in Surabaya is an educational destination with the potential to introduce Indonesia's maritime history to elementary school students. However, the lack of engaging supporting materials often causes students aged 11–12 to lose focus during study tours. This project aims to design an Educational Activity Book as an interactive learning tool to support historical education during museum study tours. The design method involves needs analysis using the 5W1H approach and the application of educational graphic design principles. The book is designed with a cartoon and flat illustration style, and is equipped with interactive elements such as stickers, pin buttons, collectible cards, posters, and keychains as rewards. The final product is expected to assist teachers in guiding students, increase active participation, and make history learning more enjoyable while encouraging curiosity and exploration during museum visits.